2011
DOI: 10.1108/02632771111178364
|View full text |Cite
|
Sign up to set email alerts
|

Preferred risk allocation in target cost contracts in construction

Abstract: Purpose -The purpose of this paper is to identify the party most preferred to take the risks associated with the Target Cost Contracts and Guaranteed Maximum Price Contracts (TCC/GMP) in the Hong Kong context. Design/methodology/approach -An empirical questionnaire survey was conducted with the relevant industrial practitioners to solicit their preferences of risk allocation in TCC/GMP construction projects in Hong Kong. Findings -The survey findings indicated that risks on tender documentation and project des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
4
14
0
Order By: Relevance
“…Another on-going research project looking at the identification of key risk factors and risk mitigation measures, together with the evaluation of various risk sharing mechanisms for GMP/TCC projects is now being launched in Hong Kong (Chan et al, 2008) and the key research findings will be compiled later via publications (e.g. Chan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another on-going research project looking at the identification of key risk factors and risk mitigation measures, together with the evaluation of various risk sharing mechanisms for GMP/TCC projects is now being launched in Hong Kong (Chan et al, 2008) and the key research findings will be compiled later via publications (e.g. Chan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We hope that the research study will stimulate a wider debate on the underlying benefits associated with GMP/TCC in both local and international contexts for reference by the construction industry at large. Another research project focusing on risk identification, risk analysis, risk mitigation, and risk allocation inherent with GMP/TCC contracts have been completed recently in Hong Kong, Australia, and the United Kingdom (Chan et al, 2008b) and the key research findings have been reported in other publications (e.g., Chan et al, 2010a;2011c).…”
Section: Discussionmentioning
confidence: 99%
“…To develop a proper incentive arrangement, Badenfelt (2008) recommended that the contracting parties collect trustworthy data about each other's skills, reputation and target time. Based on a survey, Chan et al (2011) suggested that any time incentive arrangement should be established based on risk control ability of both agent and client. Carmichael (2013a, b and2014) addressed the optimal incentive problem in construction projects with a single agent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using principal-agent theory Chang (2013) investigated the consequence of contract breakup into risk allocation decisions. Chan et al (2011) Despite an extensive body of publications on time incentive contracts, a review of the literature, as shown in Table 1, reveals that few studies have examined the influence of factors affecting the choice of a time incentive arrangement (Al-Subhi Al-Harbi, 1998;Broome and Perry, 2002;Badenfelt, 2008;Carmichael, 2013a, b and2014). No literature appears to have focused on the optimal time incentive compensation arrangement in contracts with multiple agents.…”
Section: Literature Reviewmentioning
confidence: 99%